Changes in Relationship Dynamics in Men and Women After Receiving the Diagnosis of Breast Versus Prostate Cancer: A Population-based Study - Frederick Heath, BS; Kyle Ockerman, BS; Gayle S. Wiesemann, MD; Rachel Safeek, MD; Marie Heath, BS; Arash Momeni, MD; Lisa R. Spiguel, MD; Stephen Kovach, MD; Sarah Sorice-Virk, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. Relationship changes after cancer are prevalent yet underexplored. This investigation aimed to assess factors influencing relationship changes between participants receiving the 2 most common gender-specific cancer diagnoses: breast and prostate. Methods:. Anonymous surveys were administered via Amazon Mechanical Turk. Eligible participants were 18 years or older and diagnosed with breast or prostate cancer. Relationship satisfaction and mental health were assessed via Personal Health Questionnaire Depression Scale (PHQ-8), General Anxiety Disorder (GAD-7), and Self-Esteem and Relationship Questionnaire. Results:. Of the 186 study respondents, 85.4% (159) had breast cancer and 14.5% (27) had prostate cancer. More breast cancer participants reported that their relationship worsened after cancer diagnosis (breast: 40.9%, prostate: 11.1%), whereas a majority of prostate cancer patients reported improved relationships (breast: 17%, prostate: 66.7%; P < 0.001). However, most participants reported no relationship status change (breast: 66.7%, prostate: 77.8%; P = 0.508) and remained with the same partner postdiagnosis (breast: 84.9%; prostate: 77.8%). Breast cancer participants reported higher self-esteem compared with prostate cancer participants (P = 0.019). There was no significant difference in overall Self-Esteem and Relationship Questionnaire (P = 0.140), PHQ-8 (P = 0.689), and GAD-7 (P = 0.871) scores. Average PHQ-8 and GAD-7 scores indicated moderate depression (breast: 12.62, prostate: 12.88) and moderate anxiety (breast: 10.96, prostate: 11.06). Conclusions:. Breast cancer participants reported greater perceived changes in their relationship postdiagnosis. This study supports routine, active, and pre-emptive involvement of a mental health provider for patients with cancer to improve mental health outcomes.